A novel approach for stability and transparency control of nonlinear bilateral teleoperation system with time delays. (February 2016) - Sun, Da; Naghdy, Fazel; Du, Haiping
Abstract: In this paper, a novel control approach is presented to improve the stability and transparency of the nonlinear bilateral teleoperation system with time delays, where a four-channel (4-CH) architecture using modified wave reflection reduction transformation is explored in order to guarantee the passivity of the communication channels in the nonlinear bilateral teleoperation system; a sliding-mode controller is proposed to compensate for the dynamic uncertainties and enhance the system synchronization performance in finite time. The system stability has been analyzed using Lyapunov functions. The proposed method is validated through experimental work based on a 3-DOF bilateral teleoperation platform in the presence of time delays. The experimental results clearly demonstrate that the proposed control algorithm has superiority on system transparency over other wave-based systems.